Enhancing performance of microbial fuel cells by using novel double-layer-capacitor-materials modified anodes. (18th January 2018) - Chen, Wenwen; Liu, Zhongliang; Hou, Junxian; Zhou, Yu; Lou, Xiaoge; Li, Yanxia
Abstract: Super-capacitor (SC) activated-carbon (AC) carbon-nanotubes (CNTs) (SC-AC-CNTs) is a kind of AC-based composite material and it combines the advantages of carbon nanotubes and activated carbon, including a series of peculiar properties such as low charge transmission resistance, super large specific area and excellent power characteristic. In this study, SC-AC-CNTs are first used to modify the carbon cloth (CC) anodes of microbial fuel cells (MFCs) and compared with that of SC-AC and CC. The measurements show that the specific surface area is increased from 219.519 m 2  g −1 to 283.643 m 2  g −1 after modification. The new anode is assembled in a urine-powered MFC (UMFC) to test its effectiveness. It is found that the amount of microorganisms attached on the new anode is much larger than that on the blank anode in UMFC. The maximum power densities of the UMFC assembled with SC-AC-CNTs and SC-AC modified anodes are 899.52 mW m −2 and 555.10 mW m −2, which are 2.9 and 1.8 times of that of the blank UMFC, respectively. The tests also shows that the UMFC with SC-AC-CNTs-modified anode creates a much longer duration of 105 h at high-voltage plateau in a single cycle that is about 2–3 times of the other two groups. These findings demonstrate that these two double layer capacitor materials can effectively boost overall MFC performance. Highlights: Super-capacitor activated-carbon carbon-nanotubes was used to modify MFC anode. The power densities of SC-AC-CNTs/CC UMFC was 2.9 times of that of the blank MFC. A longer duration at high-voltage plateau (2–3 times of the other MFCs) was achieved.